The Discourse of Reservations to CEDAW on Women’s Rights in Malaysia, Brunei, and Indonesia - Saraswati, Ayu Nanda, Anak Agung (Indonesian Journal of International Law, 2022)
Substantive religious-based reservations towards CEDAW have been made by a number of states. Unfortunately, this type of reservations can also have a negative effect on women’s rights. This paper intends to examine the reservation system in CEDAW, state practices and the legal consequences of reservations in general and the rights of women, particularly in South East Asia, namely Malaysia, Brunei and Indonesia. This normative research uses a statutory, conceptual and comparative legal approach. The results show that States tend to object religious-based reservations because this type of reservations is against the object and purpose of the treaty. Whereas under international law, States are prohibited from using national (religious) law as a legitimation of failing to conduct international obligations. Although these reservations cannot be considered direct causes of discrimination and/or violation against women, some having the status of jus cogens do contribute to preserving the basic ideas of male dominance by, inter alia, maintaining the status quo and constructing it to the international legal framework. Thus, since treaties on human rights are not reciprocal in nature, countries need to agree on a mechanism that allows the fulfilment of permissible reservation thresholds, so that they stay within the object and purpose of the treaty, including the protection and the strengthening of women’s rights. Each State has the obligation, to some extent, to show the willingness and efforts that lead to the fulfilment and protection of women’s rights, which have been set out by international standards and principles.